Simulation of Full-Scale Rockfall Tests with a Fragmentation Model - Gerard Matas; Nieves Lantada; Jordi Corominas; Josep Gili; Roger Ruiz-Carulla; Albert Prades (Geosciences, 2020)
In this paper, we present the upgraded version of RockGIS, a stochastic program for the numerical simulation of rockfalls and their fragmentation, based on a fractal model. The code has been improved to account for a range of fragmentation scenarios, depending on the impact conditions. In the simulation, the parameters of the fractal fragmentation model that define the sizes of the generated fragments were computed at each impact according to the kinematic conditions. The performance of the upgraded code was verified and validated by real-scale rockfall tests performed in a quarry. The tests consisted of the release of 21 limestone blocks. For each release, the size and spatial distribution of the fragments generated by the impacts were measured by hand and from orthophotos taken via drone flights. The trajectories of the blocks and the resulting fragments were simulated with the code and calibrated with both the volume distribution and the runout distances of the fragments. Finally, as all the relevant rockfall parameters involved were affected by strong uncertainty and spatial variability, a parametric analysis was carried out and is discussed.